A WAKE CALL TO SEEING THE POTENTIALS OF AUTONOMOUS VEHICLES IN REVOLUTIONIZING INTELLIGENT TRANSPORTATION SYSTEMS IN NIGERIA: A MIXED-METHOD APPROACH - Sanctus, Emekumeh Okpala; Edje, Abel E. (FUDMA Journal of Sciences, 2026)
The adoption of autonomous vehicle (AVs) has sparked considerable interest across diverse industries, including public transportation, underground mining, and agriculture sectors. The autonomous vehicle is about to hit the mass-market. The question is not about when it will happen but in which conditions, under which form or who will be the first autonomous vehicle manufacturer to release an efficient and reliable final product in Nigeria. By now, the equation has not been solved, due to the high price of the technologies needed, the lack of solutions to provide a reliable network, and the necessity to change conventions established before now in terms of responsibility of drivers. Nevertheless, the autonomous vehicle is not only an evolution of a previous product, which is able to evaluate and to progressively transform into a self-driven vehicle. This innovation is one step further and is challenging everything that had been established until now in terms of objective criteria expected from a vehicle. This is why it was called a disruptive innovation, or even a revolution, in the sense that it has the power to totally change the way we interact with our everyday transportation system. To enter into the market, this technology, will have to overcome some challenges, on the technological side but also on the psychological side of his future clients. Therefore, an heterogeneous method approach was employed, hybridizing quantitative data from surveys of approximately 2000 randomly selected individuals and qualitative insights from in-depth interviews with policymakers, traffic engineers, and industry representatives.